Molecular Inferences Suggest Multiple Host Shifts of Rabies Viruses from Bats to Mesocarnivores in Arizona during 2001–2009 - Kuzmin, Ivan V.; Shi, Mang; Orciari, Lillian A.; Yager, Pamela A.; Velasco-Villa, Andres; Kuzmina, Natalia A.; Streicker, Daniel G.; Bergman, David L.; Rupprecht, Charles E. (PLoS pathogens, 2012)
In nature, rabies virus (RABV; genus Lyssavirus, family Rhabdoviridae) represents an assemblage of phylogenetic lineages, associated with specific mammalian host species. Although it is generally accepted that RABV evolved originally in bats and further shifted to carnivores, mechanisms of such host shifts are poorly understood, and examples are rarely present in surveillance data. Outbreaks in carnivores caused by a RABV variant, associated with big brown bats, occurred repeatedly during 2001-2009 in the Flagstaff area of Arizona. After each outbreak, extensive control campaigns were undertaken, with no reports of further rabies cases in carnivores for the next several years. However, questions remained whether all outbreaks were caused by a single introduction and further perpetuation of bat RABV in carnivore populations, or each outbreak was caused by an independent introduction of a bat virus. Another question of concern was related to adaptive changes in the RABV genome associated with host shifts. To address these questions, we sequenced and analyzed 66 complete and 20 nearly complete RABV genomes, including those from the Flagstaff area and other similar outbreaks in carnivores, caused by bat RABVs, and representatives of the major RABV lineages circulating in North America and worldwide. Phylogenetic analysis demonstrated that each Flagstaff outbreak was caused by an independent introduction of bat RABV into populations of carnivores. Positive selection analysis confirmed the absence of post-shift changes in RABV genes. In contrast, convergent evolution analysis demonstrated several amino acids in the N, P, G and L proteins, which might be significant for pre-adaptation of bat viruses to cause effective infection in carnivores. The substitution S/T₂₄₂ in the viral glycoprotein is of particular merit, as a similar substitution was suggested for pathogenicity of Nishigahara RABV strain. Roles of the amino acid changes, detected in our study, require additional investigations, using reverse genetics and other approaches.